(untitled) (Triwikrama: Jurnal Ilmu Sosial, 2025)
This article focuses on South Korea’s position amid fierce rivalry between the United States and China. The purpose of this study is to analyze how South Korea adapts and responds to the dynamics of strategic rivalry between the United States and China in East Asia. This article will explain the security alliance between South Korea and the United States. In addition, the dynamics between China and South Korea will also be discussed in this article, particularly how South Korea responds to pressure and coercive actions taken by China against South Korea. This article will also explain the strategies and policies implemented by South Korea to maintain its strategic interests amid the alliance dilemma formed between the three countries, such as the hedging strategy that is key to balancing the two major powers for the sake of South Korea’s national interests.